Podcast With Peer Assisted Learning: Does It Really Affect Students’ Listening Comprehension Skills? - Silmawati Silmawati; Asnawi Muslem; Iskandar Abdul Samad (English Education Journal, 2018)
Integrating Podcasts with Peer-Assisted Learning into English classes might be able to improve the listening abilities of EFL students. This system is ideal for senior high school students, who mostly still experience difficulties with listening comprehension, to be more enthusiastic in the learning process. This research aimed at determining the effect of using Podcast with Peer-Assisted Learning on students’ listening comprehension, discovering the possible difference between male and female students in achieving better results in learning listening comprehension and figuring out their motivation in learning with this treatment.